1972
DOI: 10.1159/000130218
|View full text |Cite
|
Sign up to set email alerts
|

Translocation heterozygosity and associated subfertility in man

Abstract: Details of meiotic chromosome studies in four human male translocation heterozygotes are given. All are associated with subfertility. One Robertsonian translocation and one reciprocal autosome translocation appear to be associated with increased levels of abortion. Segregation of unbalanced gametic genomes is thought to be the underlying cause of fetal death. Two other reciprocal autosome translocations are associated with gametogenic failure, leading to azospermia in male heterozygotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 4 publications
3
36
1
1
Order By: Relevance
“…Kjessler (1966) noted an inverse correlation between chromosome anomalies and sperm counts in infertile males. In the following years several surveys were carried out after banding techniques had become routine and confirmed that infertile males have a higher prevalence of abnormal karyotypes compared to unselected male newborns (Chandley et al, 1972;Retief et al, 1984;Bourrouillou et al, 1985;DeBraekeleer and Dao, 1991;Guichaoua et al, 1993;Pandiyan and Jequier, 1996).…”
Section: Copyright © 2005 S Karger Ag Baselmentioning
confidence: 98%
“…Kjessler (1966) noted an inverse correlation between chromosome anomalies and sperm counts in infertile males. In the following years several surveys were carried out after banding techniques had become routine and confirmed that infertile males have a higher prevalence of abnormal karyotypes compared to unselected male newborns (Chandley et al, 1972;Retief et al, 1984;Bourrouillou et al, 1985;DeBraekeleer and Dao, 1991;Guichaoua et al, 1993;Pandiyan and Jequier, 1996).…”
Section: Copyright © 2005 S Karger Ag Baselmentioning
confidence: 98%
“…An association between human male infertility and chromosomal anomalies has been known for a long time [56,57]. The incidence of karyotype abnormalities among patients with infertility has been reported to range between 2% to 21%, being low among azoospermic men [58][59][60].…”
Section: Molecular Insight Into Male Infertilitymentioning
confidence: 99%
“…There are now a number of conflicting reports on the effects of Robertsonian translocations on the fertility of man (Chandley et al, 1972;Fraccaro et al, 1973;Palmer et al, 1973) and domestic animals (Gustavsson, 1969;Pollock & Bowman, 1974;Bruère & Chapman, 1974;Bruère, 1974aBruère, , b, 1975. It has been assumed that non-disjunction of the homologues of the translocation chromosomes at anaphase I is a regular occurrence in translocation hétéro¬ zygotes, and that a proportion of the unbalanced secondary spermatocytes become mature gametes.…”
Section: Introductionmentioning
confidence: 99%